LIGHTWEIGHT OPTIMIZATION OF VEHICLE FRAME STRUCTURE BASED ON THE KRIGING APPROXIMATE MODEL - REN Ming; SUN Tao; SHI YongJin; ZHENG SongLin; LI YuGang (Jixie qiangdu)
In order to reduce the weight of the frame and improve the static and dynamic performance of frame structure,the structure parameters of frame beam,crossbeam were served as the design variables,sampling points were obtained by using optimal Latin squares design of experimental method. The Kriging method was adopted for the multi-objective system of the frame NVH,torsional stiffness,bending stiffness and frame quality,an approximate model was optimized by using NSGA,and then the Pareto optimal solution set was obtained.